Board gender diversity, corporate governance and bank efficiency in Ghana: a two-stage data envelope analysis (DEA) approach - David Adeabah; Agyapomaa Gyeke-Dako; Charles Andoh (Corporate Governance: The International Journal of Business in Society, 2018)
This study analyses the efficiency of banks under board gender diversity and examines the determinants of bank efficiency. Using a two-step framework, the first stage result shows that banks experience about 7.9 per cent improvement in their efficiency with board gender diversity on average. The second stage regression results reveal that gender diversity promotes bank efficiency up to a maximum of two female directors on a nine-member board, suggesting a threshold effect on bank efficiency. Board size improves bank efficiency. Board independence is negatively related to bank efficiency. Also, we find that powerful CEOs are detrimental for bank efficiency. Finally, we find that ownership structure, bank size, bank age and loan-to-deposit ratio are important factors affecting bank efficiency. The paper contributes to bank governance structure, namely gender composition of boards and provides an insight for regulators and shareholders to estimate the role of men and women on boards.
Keywords: 330; Board Gender Diversity; Corporate Governance; Bank Efficiency; Ghana